Method for extracting vanadium and titanium from vanadium-containing titanium slag - WANG LINA; QI TAO; ZHAO HONGXIN; LIU YAHUI; WANG WEIJING; CHEN DESHENG; YU HONGDONG (2015)
The invention belongs to the field of hydrometallurgy, and relates to a method for extracting vanadium and titanium from vanadium-containing titanium slag. The method comprises the following steps that (1) vanadium-containing titanium slag, oxidizing agents and hydrochloric acids are subjected to mixed leaching, and vanadium-containing acid leaching liquid and titanium-rich materials are obtained; (2) reducing agents are added into the vanadium-containing acid leaching liquid to obtain a reducing solution; (3) the pH value of the reducing solution is regulated to obtain extraction raw liquid; (4) the extraction raw liquid is subjected to extraction to obtain a vanadium-containing organic phase; (5) the vanadium-containing organic phase is subjected to reverse extraction to obtain a vanadium solution; (6) the vanadium solution is prepared into vanadium oxide; (7) titanium-rich materials obtained in the first step take reaction with an alkaline solution, and water washing titanium slag is obtained after the water washing; (8) the water washed titanium slag is subjected to acid washing to obtain acid-soluble titanium slag. The method provided by the invention has the advantages that the problems of high-temperature multi-time calcination, high energy consumption, serious three-waste pollution and the like of the traditional vanadium extraction process are avoided; the anosovite structure in the vanadium-containing titanium slag can be damaged in the process, the vanadium leaching rate is greatly improved, and the efficient leaching of the vanadium and the efficient extraction of the vanadium and titanium are realized.